The Role Of The Manager In Creating Modern Management - Shoxbek Ergashev (Genius Journals, 2024)
This article discusses the fact that a manager should have the qualities of an organizer, educator, researcher, and administrator, that a manager should achieve a high level of culture of the management process and improve the organization of his work.
Keywords: Culture; management; education